2003
DOI: 10.1098/rspb.2003.2445
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against perceptual bias views for symmetry preferences in human faces

Abstract: Symmetrical human faces are attractive. Two explanations have been proposed to account for symmetry preferences: (i) the evolutionary advantage view, which posits that symmetry advertises mate quality and (ii) the perceptual bias view, which posits that symmetry preferences are a consequence of greater ease of processing symmetrical images in the visual system. Here, we show that symmetry preferences are greater when face images are upright than when inverted. This is evidence against a simple perceptual bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
106
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 36 publications
17
106
2
2
Order By: Relevance
“…Third, facial symmetry may provide valid cues to mate quality (Thornhill & Møller 1997;Rhodes & Zebrowitz 2002; but see Rhodes et al 2001b). Little & Jones (2003) have reported a preference for facial symmetry in upright but not inverted faces, which they interpret as an adaptation for mate choice. Alternatively, their results could reflect the greater difficulty of detecting symmetry in inverted faces, which are rarely seen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, facial symmetry may provide valid cues to mate quality (Thornhill & Møller 1997;Rhodes & Zebrowitz 2002; but see Rhodes et al 2001b). Little & Jones (2003) have reported a preference for facial symmetry in upright but not inverted faces, which they interpret as an adaptation for mate choice. Alternatively, their results could reflect the greater difficulty of detecting symmetry in inverted faces, which are rarely seen.…”
Section: Methodsmentioning
confidence: 99%
“…In mate choice, humans are very sensitive to facial asymmetries (Møller & Swaddle 1997;Rhodes et al 1998;Simmons et al 2004). They find symmetric faces attractive (Rhodes et al 1998(Rhodes et al , 1999Mealey et al 1999;Perrett et al 1999;Rhodes & Zebrowitz 2002;Little & Jones 2003), and they interpret symmetry as a sign of important aspects of mate quality, such as health and intelligence (Rhodes et al 2001b;Rhodes & Zebrowitz 2002;Zebrowitz & Rhodes 2004). To the extent that symmetry is a valid signal of mate quality, a preference for facial symmetry may be an adaptation for finding highquality mates (Møller & Swaddle 1997;Thornhill & Gangestad 1999;Fink & Penton-Voak 2002;Little & Jones 2003), in which case specialized mechanisms may have evolved (Williams 1966).…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of the investigations focused on IA has been the characterization of the "deviation" of a normal bauplan, as a response to a wide array of factors such as sexual selection (Gangestad et al, 2001(Gangestad et al, , 2010, .. heavy working conditions .~d socioeconomic status (Ozener and Fink, 2010;Ozener, 2010a), or attractiveness (Scheib et al, 1999;Gangestad and Thornhill, 2003;Little and Jones, 2003;Rhodes et al, 2009;Zaidel and Hessamian, 2010;Neby and Ivar, 2013). In addition, DA has been reported in humans (Mcintyre and Mossey, 2002;Schaefer et al, 2006;DeLeon, 2007;Ercan et al, 2008;Klingenberg et al, 2010b), although it is considered a subtle phenomenon.…”
mentioning
confidence: 99%
“…Research that has explored the effect of inversion on facial symmetry illustrates the difficulties of making conclusions based on 2afc tasks. Little and Jones [12] showed no symmetry preference for inverted faces suggesting that when the task is difficult there is a reduced preference. This has two possible conclusions.…”
Section: Symmetry Detection Versus Symmetry Preferencementioning
confidence: 97%
“…Many studies have demonstrated that more symmetrical faces are more attractive (e.g., [9,10]). There has also been debate concerning whether a general preference for symmetry derives from an evolutionary preference for symmetrical mates or whether the evolutionary preference is just a feature of a general preference for symmetry (contrast [11] and [12]). Support for this general-preference account comes from the findings that within normal populations there is, in fact, no link between health and facial asymmetry [13].…”
Section: Introductionmentioning
confidence: 99%